Investigation of the Speech Act “Request” in English and Uzbek - Khamidjonova Dilnura Mukhiddinjon qizi (Zien Journals, 2022)
This article studies the speech act “request” in Modern English and Uzbek. It also investigates expressing ways of request in the compared languages with some examples.
Keywords: speech act; pragmatics; politeness; imperative